Screening for cardiovascular risk in the general population: The SPICES implementation survey - Le Goff, Delphine; Perraud, Gabriel; Aujoulat, Paul; Deriennic, Jeremy; Guillou, Morgane; Barais, Marie; Le Reste, Jean-Yves (Frontiers in Medicine, 2023)
Background: In 2019, cardiovascular diseases (CVD) caused 32% of deaths worldwide. The SPICES survey involved five countries in an international primary CVD prevention implementation study in the general population. The French SPICES survey was implemented in the Centre Ouest Bretagne area (COB), which is a rural, economically deprived, medically underserved territory with high cardiovascular mortality. A CVD screening in the general population was needed to select the implementation population without overburdening family practitioner (FP) workforces. The efficacy and the replicability of such a screening were unknown. The aims of this study were to identify the characteristics of the individuals undergoing CVD risk assessment with the Non-Laboratory Interheart risk score (NL-IHRS),and to identify barriers and explore facilitators when screening the general population.. Method: An implementation study combining a cross-sectional descriptive study with qualitative interviews was undertaken. The NL-IHRS was completed by trained screeners selected from health students, pharmacists, nurses, and physiotherapists in the area with a dedicated e-tool in sport and cultural events and public places. After the screening, all screener groups were interviewed until theoretical saturation for each group. Thematic analysis was performed using double-blind coding. Results: In 5 months, 3384 assessments were undertaken in 60 different places, mostly by health students. A total of 1587, 1309, and 488 individuals were at low, moderate, and high CVD risk. Stressed or depressed individuals were remarkably numerous (40.1% and 24.5% of the population, respectively). Forty-seven interviews were conducted. The main facilitators were willingness of the population, trust between screeners and the research team, and media publicity. The main barriers were lack of motivation of some screeners, some individuals at risk, some stakeholders and difficulties in handling the e-tool. Conclusion: The efficacy of CVD risk screening while using mostly health students was excellent and preserved the FP workforce. Replicability was highly feasible if research teams took great care to establish and maintain trust between screeners and researchers. The e-tools should be more user-friendly.